2017
DOI: 10.22278/2318-2660.2016.v40.n2.a2421
|View full text |Cite
|
Sign up to set email alerts
|

Panorama Do Câncer Em Crianças E Adolescentes Sob a Perspectiva Da Saúde Coletiva

Abstract: A assistência à saúde da criança e do adolescente necessita contemplar as particularidades e características intrínsecas a essa fase da vida. Os cânceres que acometem crianças e adolescentes têm fatores de riscos e características que diferem daqueles que acometem a população adulta. No Brasil, pouco se conhece a respeito da magnitude das neoplasias no universo infanto-juvenil, bem como as características da população acometida. Objetivou-se estudar o panorama do câncer em crianças e adolescent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…A series of side effects are caused by the treatment, and the adolescent has to face, in addition to the physical changes due to the treatments, those that are normal in the developmental phase through which they are going through. [9][10] The physical suffering resulting from the illness in the hospitalized adolescent is increased by the suffering caused by the hospitalization process, which promotes the removal of their normal activities, as well as from those people whom they love and with whom they live. 10 It is understood that adolescents undergoing cancer treatment are not accustomed to the procedures, especially those that are invasive and cause more suffering.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…A series of side effects are caused by the treatment, and the adolescent has to face, in addition to the physical changes due to the treatments, those that are normal in the developmental phase through which they are going through. [9][10] The physical suffering resulting from the illness in the hospitalized adolescent is increased by the suffering caused by the hospitalization process, which promotes the removal of their normal activities, as well as from those people whom they love and with whom they live. 10 It is understood that adolescents undergoing cancer treatment are not accustomed to the procedures, especially those that are invasive and cause more suffering.…”
mentioning
confidence: 99%
“…An annual incidence of around 200,000 cases is estimated worldwide, with leukemia being the most common type in this population. 9 It is revealed that, in Brazil, malignant neoplasm is one of the main causes of deaths in adolescents, being overcome only by external causes. It is known that, among cancer deaths, malignant neoplasms of lymphatic and hematopoietic tissue are the most frequent, representing about 50% of cancer deaths in the age group of ten to 14 years and 40% of the group of 15 to 19 years.…”
mentioning
confidence: 99%
See 3 more Smart Citations